Analysis of Clinical Predictive Factors Affecting the Outcome of Second-Line Chemotherapy for Gemcitabine-Refractory Advanced Pancreatic Cancer - Lee, Jeung Eun (Gut Liver, 2020)
BACKGROUND/AIMS: The benefit of second-line chemotherapy (SL) after failed first-line chemotherapy (FL) in patients with advanced pancreatic cancer has not yet been established. We evaluated the clinical characteristics affecting the benefits of SL compared to best supportive care (BSC), identified the prognostic factors, and ultimately devised a model of clinical parameters to assist in making decision between SL and BSC after the failure of gemcitabine-based FL. METHODS: The records of patients who received gemcitabine-based FL for advanced pancreatic cancer at Yonsei University Hospital between January 2010 and December 2015 were retrospectively reviewed. Significant clinical parameters were assessed for their potential as predictive factors. RESULTS: SL patients received a longer duration of FL compared with BSC patients with median duration being 16.0 weeks (range, 8.0 to 26.0 weeks) and 8.0 weeks (range, 4.0 to 16.0 weeks), respectively (p<0.001). When the SL group was stratified by their modified overall survival (mOS) (longer and shorter than 6 months), we found significant differences for several clinical factors, namely, metastasis to the peritoneum (p<0.001), number of metastases (p<0.001), thrombotic events (p=0.003), and level of carbohydrate antigen 19-9 (CA19-9; p=0.011). In multivariate analysis, more than one site of metastasis, occurrence of thrombotic event during FL, and a CA19-9 level above 90 U/mL were significant independent prognostic factors for mOS in the SL group (p<0.05). When an attempt was made to devise a prognostic nomogram, Harrell’s C-index of the final prognosis prediction model was 0.62. CONCLUSIONS: SL may be beneficial for patients without peritoneal metastasis or thrombotic events who have a single metastasis and a level of CA19-9 less than 90 U/mL. This prognostic nomogram can be used to predict mOS before the administration of SL after the failure of gemcitabine-based FL.